2015
DOI: 10.1017/jfm.2015.492
|View full text |Cite
|
Sign up to set email alerts
|

Vortex-ring-induced stratified mixing

Abstract: There is tantalizing evidence that some mechanically driven stratified flows tend towards a state of constant mixing efficiency. We provide insight into the energy balance leading to the constant mixing efficiency and isolate the responsible mechanism. The work presented demonstrates an important mixing efficiency regime for periodically forced externally driven stratified flows. Externally forced stratified turbulent mixing is often characterized by the associated eddies within the flow, which are the dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
4
15
0
Order By: Relevance
“…The vortex tube was inserted to an approximate depth of 0.13m. This setup is similar to that found in Olsthoorn & Dalziel (2015). In both the vertical-slice measurements found here and the horizontal-slice measurements found below, the base of the vortex tube was always positioned at least two vortex diameters away from the density interface.…”
Section: Vertical-slice Observationssupporting
confidence: 82%
See 2 more Smart Citations
“…The vortex tube was inserted to an approximate depth of 0.13m. This setup is similar to that found in Olsthoorn & Dalziel (2015). In both the vertical-slice measurements found here and the horizontal-slice measurements found below, the base of the vortex tube was always positioned at least two vortex diameters away from the density interface.…”
Section: Vertical-slice Observationssupporting
confidence: 82%
“…The stratification was generated using a peristaltic pump to slowly inject the denser fluid (ρ 2 ) beneath a layer of less dense fluid (ρ 1 ). This methodology has been previously shown to produce sharp interfaces (Olsthoorn & Dalziel 2015). Typically, these two fluid layers would have different refractive indexes, which distort the camera images.…”
Section: Vertical-slice Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the other end of the spectrum, strong stratification leads to an entrainment velocity u e /u ∝ Ri −1 b in the experiments by Kato and Philipps (1969). Hence a constant mixing efficiency follows, as has been confirmed by several more recent strongly stratified turbulence experiments (see Olsthoorn and Dalziel (2015) and references therein). In the research work of Shih et al (2005) a constant mixing coefficient Γ ≈ 0.2 was found for buoyancy Reynolds numbers in the range 7 < Re b < 100 in a series of DNS of stratified sheared turbulence but the mixing coefficient then varied as Γ ∝ Re In summary, the parameters that seem to affect mixing in stratified turbulence are the Froude number and the buoyancy Reynolds number.…”
Section: Introductionsupporting
confidence: 74%
“…In a recent study, Olsthoorn and Dalziel had compared the mixing efficiency of a sharp interface, perturbed by periodic vortex pairs [10,11]. They found that under certain flow conditions, mixing efficiency was independent of Richardson number.…”
Section: Introductionmentioning
confidence: 99%